The role of the extracellular matrix in cardiac regeneration - Xiying Wang; Shuo Yu; Lan Xie; Meixiang Xiang; Hong Ma (Heliyon)
The extracellular matrix (ECM) is a complex and dynamic three-dimensional network that functions as an architectural scaffold to maintain cardiac homeostasis. Important biochemical and mechanical signals associated with cell‒cell communication are provided via the reciprocal interaction between cells and the ECM. By converting mechanical cues into biochemical signals, the ECM regulates many cell processes, including migration, adhesion, growth, differentiation, proliferation, and apoptosis. Moreover, the ECM facilitates the replacement of dead cells and preserves the structural integrity of the heart, making it essential in conditions such as myocardial infarction and other pathological states. When excessive ECM deposition or abnormal production of ECM components occurs, the heart undergoes fibrosis, leading to cardiac dysfunction and heart failure. However, emerging evidence suggests that the ECM may contribute to heart regeneration following cardiac injury. The present review offers a complete overview of the existing information and novel discoveries regarding the involvement of the ECM in heart regeneration from both mechanical and biochemical perspectives. Understanding the ECM and its involvement in mechanotransduction holds significant potential for advancing therapeutic approaches in heart repair and regeneration.